The Analysis of Equivalence of Song Lyrics from English to Indonesian Song By Maher Zain - Sofianti, Yana; Baharudin, Baharudin; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2025)
This study aims to examine and analyses the equivalence of meaning between English and Indonesian lyrics of three Maher Zain songs: "For the Rest of My Life," "I Love You So," and "Guide Me All the Way." In line with that, by applying Eugene Nida's theory of formal and dynamic equivalence and Peter Low's Pentathlon Principle as a reference in determining the extent to which the translation maintains the meaning, emotion, and musical beauty that are equivalent to the original version. The analysis was carried out on each line of the English and Indonesian lyrics with a qualitative approach, then a comparison was made referring to meaning, convention, naturalness of language, rhythm, and rhyme. The research findings show in detail that dynamic equivalence is the most dominant. This is because the translator emphasizes and focuses on conveying emotional and spiritual messages that are appropriate or suitable for the culture and sensitivity of Indonesian listeners. On the other hand, in simpler parts and those containing theological meaning, the use of formal equivalence aims to ensure clarity and accuracy. Furthermore, regarding the meaning, naturalness, and loudness of the song translation, it is considered successful based on the Pentathlon Principle analysis, although there are slight differences in rhythm and cadence caused by structural differences and language rules. Finally, the results of the data comparison in this study show that the translation of Maher Zain's songs has succeeded in balancing the equality of the original meaning and musical and cultural. In addition, especially the translation of religious songs requires linguistic accuracy, cultural sensitivity, and harmony.